Development of STEM (Science, Technology, Engineering, and Mathematics) Based E-Modules to Improve Student Collaboration Skills - Nurfazlina; Muhammad Arsyad; Khaeruddin (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a STEM-based physics e-module as innovative teaching material to improve students’ collaboration skills. The research used a Research and Development (R&D) method with a 4D model consisting of Define, Design, Develop, and Disseminate stages. The research subjects included three expert validators, ten physics teachers as practitioners, and thirty students from class X.B of SMA Muhammadiyah 1 Unismuh Makassar. Data were collected using validation sheets, practitioner questionnaires, and collaboration skill tests based on the Situational Judgment Test (SJT), which measured four indicators: cooperation, communication, problem solving, and responsibility. The results showed that the STEM-based e-module met the criteria of validity, practicality, and effectiveness. The validation results obtained an average Aiken’s V index of 0.93 (valid category). Practitioner assessments showed an average practicality score of 96.6% (very practical), while the effectiveness test using N-Gain analysis reached 0.84 or 84% (high category). These findings indicate that the developed STEM-based e-module is valid, practical, and effective for improving students’ collaboration skills in physics learning.